Crime-Induced Business Relocations in the Austin (Texas) Metropolitan Area, 1995-1996 - Huff, David Lynch ([Verlag nicht ermittelbar], 2001)
There were three key objectives to this study: (1) to determine the relative importance of crime-related as well as business-related factors in business relocation decisions, including business ownership, type of business, and business size, (2) to ascertain how businesses respond to crime and fear of crime, such as by moving, adding more security, requesting police protection, or cooperating with other businesses, and (3) to identify the types of crime prevention measures and assistance that businesses currently need and to assess the roles of business associations and police departments in providing enhanced crime prevention assistance. From November 1995 through February 1996 a mail survey was distributed to a sample of three different groups of businesses in Austin's 14 highest crime ZIP codes. The groups consisted of: (1) businesses that remained within the same ZIP code between 1990 and 1993, (2) new firms that either moved into a high-crime ZIP code area between 1990 and 1993 or were created in a high-crime ZIP code between 1990 and 1993, and (3) businesses that relocated from high-crime ZIP code areas to other locations in Austin's metropolitan area or elsewhere in Texas. Variables include type of business, ownership of business, number of employees, reasons for moving or staying in neighborhood, types of crime that affected business, owner's response to business crime, customer safety, and the role of business associations and the police in preventing crime.